Seasonal variation in body size of tropical anuran amphibians - da Silva, Fernando Rodrigues [UNESP]; Rossa-Feres, Denise de Cerqueira [UNESP] (My University, 2010)
Most anurans are considered short lived reproducing only once, with adult size being an important factor contributing to mating success. We sampled anurans with 30 pitfall traps in three forest patches of the northwestern São Paulo State, Brazil, throughout one year. Our objective was to analyze the variation in anuran body size between the dry and rainy season. Our hypothesis is that anurans registered during the rainy season will be larger than conspecifics registered during dry season, since there is a selective advantage in having a larger body size during reproduction activity. The most abundant species registered in the patches were Eupemphix nattereri, Physalaemus cuvieri and Leptodactylus podicipinus. Males and females of E. nattereri and P. cuvieri recorded in the rainy season were larger than of those captured in the dry one. In contrast, males of L. podicipinus were larger in the dry season than in the rainy season. Besides, the operational sex ratio (OSR) in the breeding season was biased towards males in these three species with, respectively, 4.66, 3.2 and 1.87 males per female. Our results suggest that probably body size variation between different seasons is a consequence of individuals' turnover between rainy seasons. Lower individuals captured in the dry season, would be reproductively active adults in the next breeding season.
Keywords: Mesophytic semideciduous forest; Recruitment; Seasonality; Success of reproduction